2019
DOI: 10.1515/jpem-2018-0236
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of cardiorespiratory fitness and abdominal resistance are associated with metabolic risk in schoolchildren

Abstract: Background Low levels of physical fitness are associated with metabolic disorders in adults. However, this relationship has been little explored in children and adolescents. The aim of the present study was to investigate whether there is an association between physical fitness related to health and the presence of metabolic risk in schoolchildren. Methods The sample for this cross-sectional study was composed of 1251 schoolchildren of both genders between 7 and 17 years of age. Three indicators of physical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Similarly, previously epidemiologic studies have shown that youths with low body fat and low cardiorespiratory fitness (CRF) were at high cardiovascular risk than those with high body fat and adequate CRF [8,9]. Excessive body fat and low CRF are associated with a list of severe diseases, including metabolic disorders [10,11], independently of weight status or dietary intake [12]; however, it is not entirely clear if the interrelationships among CRF, body composition and low-grade inflammation in adolescents are independent or partly due to the mediating effect of excessive adiposity, since the current literature is limited and/or equivocal [13,14]. Moreover, the effects of CRF combined with body composition on subclinical inflammation during the adolescence are unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, previously epidemiologic studies have shown that youths with low body fat and low cardiorespiratory fitness (CRF) were at high cardiovascular risk than those with high body fat and adequate CRF [8,9]. Excessive body fat and low CRF are associated with a list of severe diseases, including metabolic disorders [10,11], independently of weight status or dietary intake [12]; however, it is not entirely clear if the interrelationships among CRF, body composition and low-grade inflammation in adolescents are independent or partly due to the mediating effect of excessive adiposity, since the current literature is limited and/or equivocal [13,14]. Moreover, the effects of CRF combined with body composition on subclinical inflammation during the adolescence are unclear.…”
Section: Introductionmentioning
confidence: 94%
“…The characteristics of the 13 studies included in the review are shown in Table 1. Seven studies were carried out in the southern region, with three studies in the state of Paraná 20,29,31 , two studies in Santa Catarina 19,22 and two studies in Rio Grande do Sul 26,30 . Four studies 23,25,27,28 were carried out in the northeastern region (Piauí, Bahia, Ceará and Paraíba, respectively), one study 21 was carried out in the northern region (Amazonas) and one study 24 was carried out considering all regions of the country (Northern, Northeastern, Midwestern, Southeastern and Southern).…”
Section: Resultsmentioning
confidence: 99%
“…The evaluated population covered the age group of 3-19 years. Eleven studies had cross-sectional design [19][20][21][22][23][24][25][26][27]29,30 , one study had longitudinal design 19 and one was an intervention study 28 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations